Visual Perception Of The Heritage Building Facades In The Administrative Center Area Of Malang City - Faisal Bahar (Syntax Literate, 2022)
The Administrative Center Area of Malang city, which is located around the tugu square, is one area that plays an important role in the development of the eastern part of Malang City, which has many historic buildings from the Dutch colonial heritage. The purpose of this study is to find out the similarities and differences in perceptions between the public and practitioners and academics in the field of architecture in assessing the visual elements on the historic building facades and to find out which facade visual elements are significant according to the public, practitioners, and academics in the field of architecture on the visual quality of the historic building facades in the Administrative Center Area of Malang city. Developments and constructions in the Administrative Center Area of Malang city, which do not pay attention to the area context as a historic area, can slowly cause a shift in the shape and meaning of the city structure which can affect the visual character of the building facades in the area. The shift in the visual character of the building facades that do not pay attention to the area context in a historic area can harm environmental aesthetics, causing a decrease in the visual quality of the historic area. This study uses quantitative research methods with a public perception approach. To measure people's perceptions, a differential semantic scale is used which contains two opposite words. The results show that the assessment between two groups of respondents with different occupational and educational backgrounds has the similar assessment results on each facade element. Facade elements that are significant to the visual quality of the historic building facades in the Administrative Center Area of Malang City are the facade shape and color.